ANALISIS TINGKAT KESEHATAN BANKALTIMTARA PERIODE 2012 - 2016 - -, Sahrul Hamdani (EKONOMIA, 2019)
Analysis of Bankaltimtara Health Level for the 2012-2016 period at PT Bank East Kalimantan and North Kalimantan, Samarinda (under the guidance of Mr. Robin Jonathan as supervisor I and Mrs. Ida Rahmawati as supervisor II). The purpose of this study was to determine and analyze the soundness of Bankaltimtara in the period 2012-2016 which was assessed by the CAMEL method, namely to find out and analyze Bankaltimtara Financial Performance in the period 2012-2016 from CAR (Capital Adequacy Ratio), KAP (Earning Assets Quality) , NPM (Net Profit Margin), ROA (Return On Assets), BOPO (Operating Expenses versus Operating Income) and LDR (Loan to Deposit Ratio). The basic theory used in this study is Horne & Wachowicz Jr. (2012: 2) argues that the notion of financial management is: